Premature white matter disease - Kline-Fath, Beth M.; Tkach, Jean; Merhar, Stephanie (Journal of Pediatric Neuroradiology, 2013)
Understanding the pathophysiology, imaging and correlative preterm outcome of white matter ischemic injury is important to improve neonatal clinical practices and to support preventative therapies. This article will focus on these topics in an attempt to provide greater understanding of premature white matter disease in this fragile age group.
Keywords: Prematurity; oligodendrocytes; magnetic resonance imaging; diffusion tensor imaging; magnetic resonance spectroscopy